Analisis Ketidakpastian Produksi, Harga dan Pendapatan pada Usahatani Jeruk Siam di Desa Kerta, Kecamatan Payangan, Kabupaten Gianyar - PALGUNA, I MADE ANGGI; DEWI, RATNA KOMALA; SUSRUSA, KETUT BUDI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Analysis Uncertainty Production, Price and Income of Farming Citrus Siam in Kerta Village, Payangan District, Gianyar Regency. Farming citrus siam is main source of income for most farmers in Kerta Village. The purpose of this study is to determine the source the uncertainty of farming citrus siam, the magnitude of production uncertainty, price and income also how to mitigate these uncertainty. There are several sources of uncertainty faced by farmers including sources of social uncertainty, physical uncertainty and economic uncertainty. The magnitude of uncertainty farming citrus siam there are first, production uncertainty with standard deviation is 1.616,11 kg/ha/year, then the score of coefficient variation is 0.09 and production uncertainty lower limit value is 14.764,63. Second, price uncertainty with standard deviation is 42,38 then we get the score if coefficient variation is 0,01 and price uncertainty lower limit value is Rp4.847,84. Last, income uncertainty with standard deviation in amount of Rp7.413.000,13 /ha/year, coefficient variation score is 0.11 and income uncertainty lower limit value is Rp53.863.133,07 /ha/year. The conclusion that a biggest uncertainty in farming citrus siam is income uncertainty with a value of 0,11, second largest uncertainty is production uncertainty with a value of 0,09 and the smallest uncertainty in farming citrus siam is price with a value of 0,01. In an effort to mitigate existing uncertainty with strategies for handling uncertainty sources by make regular sales, learn past mistakes, provide maximum care for plants by pruning, spraying and fertilizing and finally borrowing capital from related financial institutions. With this, farmers are expected to mitigate uncertainty in order to increase the amount of production and income of farmers in Kerta Village, Payangan District, Gianyar Regency.